Dancers and fastball sports athletes have different spatial visual attention styles - Isoglu-Alkac, Ummuhan; Ermutlu, M. Numan; Eskikurt, Gokcer; Yucesir, Ilker; Temel, Sernaz Demirel; Temel, Tan (SPRINGER, 2018)
Physical exercise and the training effects of repeated practice of skills over an extended period of time may have additive effects on brain networks and functions. Various motor skills and attentional styles can be developed by athletes engaged in different sports. In this study, the effects of fast ball sports and dance training on attention were investigated by event related potentials (ERP). ERP were recorded in auditory and visual tasks in professional dancer, professional fast ball sports athlete (FBSA) and healthy control volunteer groups consisting of twelve subjects each. In the auditory task both dancer and FBSA groups have faster N200 (N2) and P300 (P3) latencies than the controls. In the visual task FBSA have faster latencies of P3 than the dancers and controls. They also have higher P100 (P1) amplitudes to non-target stimuli than the dancers and controls. On the other hand, dancers have faster latencies of P1 and higher N100 (N1) amplitude to non-target stimuli and they also have higher P3 amplitudes than the FBSA and controls. Overall exercise has positive effects on cognitive processing speed as reflected on the faster auditory N2 and P3 latencies. However, FBSA and dancers differed on attentional styles in the visual task. Dancers displayed predominantly endogenous/top down features reflected by increased N1 and P3 amplitudes, decreased P1 amplitude and shorter P1 latency. On the other hand, FBSA showed predominantly exogenous/bottom up processes revealed by increased P1 amplitude. The controls were in between the two groups.
Keywords: Event related potentials; Fast ball sports; Dance; Spatial visual attention; NEURAL SYSTEMS; BRAIN; P300; EXERCISE; ERPS; DISCRIMINATION; PERFORMANCE; VOLUNTARY; FENCERS; LATENCY; Neurosciences & Neurology